Biodiesel Dari Limbah Ikan Baung (Mystus Nemurus) Dengan Katalis Padat H-Zeolit - Hadyan Sartoni; Syaiful Bahri; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Biodiesel  is  an  alkyl esters  of  long chain  fatty  acids  derived  from  fatty material  such as animal fat. A research synthesis of biodiesel from waste fish oil of baung into biodiesel with a solid H-zeolite catalyst. In this research review of physical properties (density, viscosity and acid number), analyzing the chemical content of biodiesel, the influence of the molar ratio of methanol  to  fish  oil  baung  the  percentage of  conversion  and  optimal  transesterification catalyst in the transesterification reaction in biodiesel synthesis. 50 grams of fish oil, versus 1:6 methanol  to oil molar, catalyst 10% of the weight of oil  input into  the biodiesel reactor and then  the process of biodiesel synthesis performed on  the operating conditions of 60 ° C temperature  and  stirring  speed of  200  rpm for  200 minutes.  The results  showed  that  the optimum  conversion  catalyst with  10% methanol  1:5 molar ratio  that is  equal to  87.02%. Physical test  results obtained by the density of 890  kg/m3, 5.48  cSt  viscosity, acid number 0.7013 mg-koh/gr sample. Results of analysis of chemical constituents by GC-MS, obtained the dominant component  in the  catalyst  biodiesel with  10% methanol  1:5 molar ratio was 51.03% oleic methyl ester, methyl ester palmitic 18.76%, 9.50% linoleic methyl ester, 4.46% stearic acid methyl ester, methyl ester 2.00% elaidic. Results obtained have characteristics approaching the characteristics of biodiesel Indonesian National Standard (SNI). Kata kunci : fish oil, Biodiesel, H-zeolite catalyst, transesterification